2014
DOI: 10.1128/jvi.02684-13
|View full text |Cite
|
Sign up to set email alerts
|

Murine Cytomegalovirus Protein pM92 Is a Conserved Regulator of Viral Late Gene Expression

Abstract: In this study, we report that murine cytomegalovirus (MCMV) protein pM92 regulates viral late gene expression during virus infection. Previously, we have shown that MCMV protein pM79 and its human cytomegalovirus (HCMV) homologue pUL79 are required for late viral gene transcription. Identification of additional factors involved is critical to dissecting the mechanism of this regulation. We show here that pM92 accumulated abundantly at late times of infection in a DNA synthesis-dependent manner and localized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 64 publications
5
17
0
Order By: Relevance
“…We can speculate, as previously suggested (32), that the vPIC may activate late gene transcription by remodeling the chromatin structure of the viral genome. Genomes of Herpesviridae associate with histones during infection and require epigenetic regulation/ modification for gene expression (41)(42)(43).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We can speculate, as previously suggested (32), that the vPIC may activate late gene transcription by remodeling the chromatin structure of the viral genome. Genomes of Herpesviridae associate with histones during infection and require epigenetic regulation/ modification for gene expression (41)(42)(43).…”
Section: Discussionsupporting
confidence: 81%
“…It appears that the phenotype of the EBV ⌬BFRF2 mutant is reminiscent of that of the EBV ⌬BcRF1 mutant (18), and like BcRF1, BFRF2 has analogs in beta-and gammaherpesviruses. These observations place the BFRF2 protein together with other EBV, CMV, and MHV-68 genes that have been characterized as being essential for late gene expression (18,(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…While WT and revertant iSLK cell lines yielded readily detectable infectious virus, iSLK-31S cells failed to yield detectable progeny virus (Fig. 1B), consistent with the described role of its orthologs in other herpesviruses (7,13,16). Immunoblot analysis showed that, compared to WT and revertant viruses, ORF31-deficient virus was specifically defective in the expression of the late gene ORF8 but not in the expression of latent (LANA) or E (K3) genes or in replication of viral DNA (Fig.…”
supporting
confidence: 83%
“…These five viral ORFs play an important role in activating viral late gene promoters, and it has also been shown that ORF30 and -34 are critical for recruiting RNA polymerase II (Pol II). More recently, studies in cytomegalovirus (CMV), a betaherpesvirus, have demonstrated that the UL79, -87, -91, -92, and -95 genes, homologous to MHV-68 ORF18, -24, -30, -31, and -34, respectively, are also essential for viral late gene expression (18)(19)(20)(21)(22). The evidence strongly suggests that beta-and gammaherpesviruses share a similar mechanism to regulate late gene expression.…”
mentioning
confidence: 99%